2013
DOI: 10.4238/2013.february.27.9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic structure among subpopulations of Gossypium mustelinum (Malvaceae)

Abstract: ABSTRACT. Gossypium mustelinum is the only cotton species native to Brazil; it is endemic to the semi-arid region of the northeast. The populations are found near perennial and semi-perennial sources of water, such as ponds or pools in intermittent streams. Problems with in situ conservation derive from human interference in its habitat, mainly because of excessive cattle grazing and deforestation. Establishing efficient strategies for in situ conservation requires knowledge of the genetic structure of the pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Population genetics studies examining tree species have shown that trees are generally allogamous, but with positive inbreeding coefficients (Azevedo et al, 2007;Santos et al, 2011;Alves et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Population genetics studies examining tree species have shown that trees are generally allogamous, but with positive inbreeding coefficients (Azevedo et al, 2007;Santos et al, 2011;Alves et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The high endogamy values (f) observed both in the overall collection as within states and multilocus F ST value show a tendency to form families progressively homozygous. Similar structures of high diversity threatened by low genetic recombination are of the others allotetraploid cottons in Brazil: G. barbadense (Almeida et al, 2009), and G. mustelinum Alves et al, 2013;Menezes et al, 2014). The limited gene flow is explained by geographical distribution of the plants, since just one to a few individuals may be find together.…”
Section: Discussionmentioning
confidence: 83%
“…The species mainly inhabits areas with longer water availability within the semiarid region in which it occurs, such as the banks of rivers and ponds. However, anthropogenic factors cause damage to the population, particularly the clearing of riparian vegetation which is usually associated with use as a pasture for cattle and goats (Alves et al, 2013). In addition, the commercial cultivation of cotton in close proximity to natural populations can introduce new problems.…”
Section: Discussionmentioning
confidence: 99%
“…There are small foci of coexistence with cultivated cotton. They result from maintenance of plants in backyards and from propagule dispersal between producing and consuming regions, with no observed impact on wild populations (Alves et al, 2013). This is an indication that impacts may depend on broader sympatry, where a greater number of cultivated individuals are within the vicinity.…”
Section: Introductionmentioning
confidence: 95%